AN EXPLORATION OF THE INCLUSION OF SOCIAL MEDIA CUSTOMER SENTIMENT BY SOUTH AFRICAN RETAIL BANKING BRAND STEWARDS FOR AN AGILE STRATEGY - Bashman, Samantha Nombulelo (The IIE, 2019)
The purpose of the study was to explore how brand stewards in the South African retail banking sector use social media conversations of consumers to create an agile brand strategy. This was an exploratory study anchored in Phenomenology. An adapted version of the Agile Manufacturing Reference model focusing on retail banking processes, people, linkages and strategy was used in this phenomenological study to measure agility levels. A total of 13 semi-structured interviews were used to collect data from retail banking brand stewards from the executive, middle management and contact staff at junior levels that had a responsibility for contributing to marketing, public relations (PR), social media and communications strategy using conversations of consumers for the banking industry. They included internal and agency staff affiliated to the banking brands. The key findings of this study include that there was no optimal strategic approach to serve a real-time marketing brand strategy and that the metrics of measurement, and the right agencies and technologies are not yet in place for a truly agile strategy. Although leaders need to continually look for innovative avenues to generate revenue, the executive level of management does not support agility and is more invested in the bottom line rather than to serve customer needs. The leaders need to embrace new technologies and avail the budget to increase resources to accommodate a digitised approach to the market in which banks operate. Although all the retail banks talk about client centricity, much of the processes, people, linkages and their strategies do not support an agile outcome. The structure must undergo considerable changes to accommodate the new digital consumer.
Keywords: Brand; Brand strategy; Social media; Digital media communication; Retail banking; Banking; Banks